INSTITUTION OF MATRIMONIAL PROPERTY – DOWRY ON THE STAGE OF MODERN EUROPE - Iveta Nikolajeva (European Scientific Journal, ESJ, 2014)
The institution of matrimonial property – dowry still exists in the EU Council Directive of 24 June 1988 (88/361/EEC) referring to the principle of free movement of capital and is a link to the Latvian Civil Law and shows the existence of the institution of dowry in European law. The study shows the background and historically evolving nature of dowry institution and evaluates the need of it in the contemporary Civil Law of Latvia, tries to answer why such an archaic legal institution is still present in the modern law, analyses it through the gender equality framework and explain regulatory failure in this context, offers solutions for this problem from the theoretical and practical perspectives. In order to understand the topic’s complexity, the article gives a short insight from the historical perspective examining the continuities and discontinuities in this social institution in different regions and eras – starting from ancient world to nowadays: from the time when the king of Babylon Hammurabi ruled up to the modern Southeast Region societies and in the Baltics. The issue has not been analyzed more widely before, there is no common understanding how it corresponds to provisions of the European Economic Community’s gender equality law and what the opinion of general public in Latvia is on this subject.